The role and therapeutic potential of mitophagy in major depressive disorder - Shi, Xin-Nuan; Liu, Chen-Yue; Li, Lin; Yao, Ming-Li; Zhong, Zhen; Jiang, You-Ming (Frontiers in Pharmacology, 2025)
Major depressive disorder, also known as MDD, affects more than 264 million people globally, making it a prevalent and critical health challenge. Traditional treatments show limited efficacy in many patients. Therefore, exploring new treatment methods is particularly crucial. Mitophagy, as a regulatory process, can help understand and treat MDD. This paper focuses on the molecular mechanisms of mitophagy, starting from proteins and related pathways, and its role in MDD. The study also explores the associations between mitophagy and neuroinflammation, oxidative stress, neurotransmitter synthesis, and neuroplasticity in MDD and discusses the progress of clinical research on the role of mitophagy in MDD. In addition, the article describes the current pharmaceutical and non-pharmaceutical interventions that can regulate mitophagy in MDD and unravels the potential and challenges of these therapeutic strategies in clinical settings. This article offers a deeper insight into the pathogenesis of MDD and offers a scientific basis for the development of new treatment strategies.